Outcome of unlinked total elbow arthroplasty for rheumatoid arthritis in patients younger than 50 years old - Keiichiro Nishida; Yoshihisa Nasu; Kenzo Hashizume; Shunji Okita; Ryuichi Nakahara; Taichi Saito; Toshifumi Ozaki; Hajime Inoue (Bone & Joint Open, 2023)
AimsThere are concerns regarding complications and longevity of total elbow arthroplasty (TEA) in young patients, and the few previous publications are mainly limited to reports on linked elbow devices. We investigated the clinical outcome of unlinked TEA for patients aged less than 50 years with rheumatoid arthritis (RA).MethodsWe retrospectively reviewed the records of 26 elbows of 21 patients with RA who were aged less than 50 years who underwent primary TEA with an unlinked elbow prosthesis. The mean patient age was 46 years (35 to 49), and the mean follow-up period was 13.6 years (6 to 27). Outcome measures included pain, range of motion, Mayo Elbow Performance Score (MEPS), radiological evaluation for radiolucent line and loosening, complications, and revision surgery with or without implant removal.ResultsThe mean MEPS significantly improved from 47 (15 to 70) points preoperatively to 95 (70 to 100) points at final follow-up (p < 0.001). Complications were noted in six elbows (23%) in six patients, and of these, four with an ulnar neuropathy and one elbow with postoperative traumatic fracture required additional surgeries. There was no revision with implant removal, and there was no radiological evidence of loosening around the components. With any revision surgery as the endpoint, the survival rates up to 25 years were 78.1% (95% confidence interval 52.8 to 90.6) as determined by Kaplan-Meier analysis.ConclusionThe clinical outcome of primary unlinked TEA for young patients with RA was satisfactory and comparable with that for elderly patients. A favourable survival rate without implant removal might support the use of unlinked devices for young patients with this disease entity, with a caution of a relatively high complication rate regarding ulnar neuropathy.Level of Evidence: Therapeutic Level IVCite this article: Bone Jt Open 2023;4(1):19–26.